Analysis of Recruitment, Selection, Compensation and Its Effect on Employee Performance Research on Yogyakarta Car Rental Employees - Catur Raharjo Noto Nagoro (Admisi dan Bisnis, 2026)
This study aims to analyze the influence of recruitment, selection, and compensation on employee performance in car rental businesses in Yogyakarta. This research is motivated by the importance of assessing the human resource management (HR) processes of recruitment, selection, and compensation in car rental companies in Yogyakarta. This study uses a quantitative approach. The population was all employees working at 13 car rental companies in Yogyakarta. The sampling technique used wasNon-Probability Sampling Saturated sampling type, with a total sample of 54 employees. Primary data was obtained through the distribution of questionnaires with a Likert scale.. The results of the data analysis indicate that the selection variable has a significant influence on the performance of car rental employees in Yogyakarta. However, the recruitment and compensation variables do not have a significant influence on the performance of car rental employees in Yogyakarta. The implication of this research is that the quality of employee performance is inseparable from the role of business leaders in the car rental sector, both in business management and operations. Therefore, good, clear, and transparent recruitment, selection, and compensation matters help car rental business owners to build strong human resources, responsive to customers, and able to contribute to business sustainability amidst increasingly competitive transportation services.